Bile Acids and Microbiome Among Individuals With Irritable Bowel Syndrome and Healthy Volunteers. Issue 1 (January 2021) - Kamp, Kendra J.; Cain, Kevin C.; Utleg, Angelita; Burr, Robert L.; Raftery, Daniel; Luna, Ruth Ann; Shulman, Robert J.; Heitkemper, Margaret M.
Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder. High bile acid (BA) profiles have been associated with abdominal pain symptoms, mucosal inflammation, and diarrhea in a subgroup of those with IBS. The purpose of this study was to compare: 1) fecal primary and secondary BAs in women with and without IBS; and 2) symptoms, gut microbiome, and diet between women with high and normal BAs (i.e., similar to healthy [HC] women). Women (ages 18–45) with IBS and HCs were recruited from healthcare providers or the community. Participants kept a 28-day symptom diary, completed a 3-day food journal, and collected a stool sample for microbiome analysis (16 S rRNA gene sequencing). Primary and secondary BA levels were determined by mass spectrometry. Primary BAs did not differ between IBS (n = 45) and HC (n = 28) groups; women with IBS had significantly increased conjugated secondary BAs (glycodeoxycholic acid [ p = 0.006], taurodeoxycholic acid [ p = 0.006], and glycolithocholic acid [ p = 0.01]). Sixty percent of women with IBS had normal BAs whereas 40% had high BAs. Women with high fecal BAs were predominantly IBS-Diarrhea or IBS-Mixed and consumed less fiber and vegetable protein and more animal protein compared to women with IBS whose fecal BAs levels were comparable to HCs. Those with high conjugated secondary fecal BAs also had a greater Firmicutes/Bacteroidetes ratio, less abundance of phylum Bacteroidete s and genus Gemmiger, and more abundance of family Erysipelotrichaceae compared to IBS women with normal BAs. Determination of fecal BA levels provides additional insights into pathophysiological links between diet and microbiome in IBS.